2015
DOI: 10.3389/fnut.2015.00034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a “Health at Every Size®”-Based Approach in Obese Women: A Pilot-Trial of the “Health and Wellness in Obesity” Study

Abstract: This study explored the effects of Health at Every Size®-based intervention on obese women by qualitatively evaluating participants’ perception toward the program and quantitatively evaluating changes related to psychological, behavioral, and body composition assessments. A prospective 1-year quasi-experimental mixed-method trial was conducted. The mixed-method design was characterized by a spiral method, and quantitative and qualitative findings were combined during the interpretation phase. The qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 37 publications
(44 reference statements)
0
31
0
2
Order By: Relevance
“…In conclusion, considering that disordered eating must be widely evaluated because of its prevalence and consequences -and must not be confused with classical eating disorder symptoms -, we need a proper instrument. DEAS had shown its possibilities in previous studies 3,34,35,52,53,54,55,56,57 , but DEAS-s provided by this study could amplify its use and bring more knowledge on dysfunctional feelings, thoughts, behaviors and relationship with food.…”
Section: Boxmentioning
confidence: 85%
“…In conclusion, considering that disordered eating must be widely evaluated because of its prevalence and consequences -and must not be confused with classical eating disorder symptoms -, we need a proper instrument. DEAS had shown its possibilities in previous studies 3,34,35,52,53,54,55,56,57 , but DEAS-s provided by this study could amplify its use and bring more knowledge on dysfunctional feelings, thoughts, behaviors and relationship with food.…”
Section: Boxmentioning
confidence: 85%
“…The nutritional sessions lasted for 45 minutes and were conducted by dietitians, who had a bachelor degree in Nutrition. A full description of the nutritional intervention may be found elsewhere [ 18 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a pilot study, we showed that a 1-year HAES ® -based intervention comprising an exercise program, nutrition counseling, and philosophical workshops led to improvements in body composition, body dissatisfaction, perception of body size, and symptoms of binge eating in addition to participants reporting behavioral and attitudinal changes towards eating and physical activity, as well as improved food choices [ 18 , 19 ]. However, the study had a quasi-experimental design, a small sample size, and did not evaluate cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that this intuitive eating app will be a more affordable and accessible way to learn how to eat intuitively as compared with in-person classes or coaching sessions. By incorporating the HBM constructs into the design, by acting as a virtual coach, with minimal barriers, using cues to action, and receiving immediate feedback, it is expected to be effective in training individuals to eat intuitively (Bacon & Aphramor, 2011;Conroy et al, 2014;Ulian et al, 2015;Van Dyke & Drinkwater, 2014). In a recent review of 26 research papers, cross sectional studies found intuitive eating to be related to healthy weight, healthy eating choices, and healthy eating behaviors (Van Dyke & Drinkwater, 2014).…”
Section: Expected Impacts On Usersmentioning
confidence: 99%